Teaching Technical Translation in the Digital Era: Challenges and Expectations - Grigoraş Cornelia-Patricia (Romanian Journal of English Studies)
Several seminar studies explain the importance of technical translation today, as 90% of the global market of translations is represented by technical translations (Kingscott 2002:247). The need for research on this was also signalled by Romanian scholars like Daniel Dejica, Loredana Pungă, Georgiana Badea, and Titela Vîlceanu (Dejica et al. 2022), who showed that there are only a few Ph.D. theses which investigate this type of LSP translation in Romania. This article is part of an ongoing Ph.D. research whose aims are: to develop effective teaching and learning methods, to focus on the state-ofthe-art teaching of technical translation today, and to highlight future research directions.